Perbandingan Usahatani Padi Sawah Sebelum dan Sesudah Pembangunan Irigasi - Sitorus, Nurmely Violita; Sitepu, Indrawaty (MuJAgri: Musamus Journal of Agribusiness, 2021)
Village development activities through irrigation development carried out by the government, at the village level, are expected to increase the income of lowland rice farmers. The purpuse this research are analyzes productivity, cost differences, and differences in income before and after irrigation development. The method of determining the area is purposive, namely in Bakarang Batu Village, Sei Bamban District, Serdang Bedagai Regency, North Sumatra. The method of determining the sample is Simple Porposive Sampling as many as 30 respondents. Methods of data analysis, namely the formula for productivity, total costs and income then analyzed using the Paired sample t-test. The results of the study were: there was a significant difference between grain productivity before and after the irrigation development program, a significant difference between production costs before and after the irrigation development program and a significant difference between the income of paddy rice farmers before and after the irrigation development program.